Analysis of nanomedicine applications for inflammatory bowel disease: structural and temporal dynamics, research hotspots, and emerging trends - Jiang, Hong-Yu; Shao, Bo; Wang, Hong-Da; Zhao, Wen-Qi; Ren, Shao-Hua; Xu, Yi-Ni; Liu, Tong; Sun, Cheng-Lu; Xiao, Yi-Yi; Li, Yi-Cheng; Chen, Qiang; Zhao, Peng-Yu; et al. (Frontiers in Pharmacology, 2025)
BackgroundThe application of nanomedicine in inflammatory bowel disease (IBD) has gained significant attention in the recent years. As the field rapidly evolves, analyzing research trends and identifying research hotpots are essential for guiding future advancements, and a comprehensive bibliometric can provide valuable insights.MethodsThe current research focused on publications from 2001 to 2024, and was sourced from the Web of Science Core Collection (WoSCC). CiteSpace and VOSviewer were employed to visualize authors, institutions, countries, co-cited references, and keywords, thereby mapping the intellectual structure and identifying emerging trends in the field.ResultsThe analysis covered 1,518 literature across 447 journals, authored by 9,334 researchers from 5,459 institutions and 287 countries/regions. The global publication numbers exhibited an upward trend, particularly in the last decade, with China leading as the top publishing country and the Chinese Academy of Sciences emerging as the foremost institution. Dr. Xiao Bo is the prominent figure in advanced drug delivery systems. This interdisciplinary field, which spans materials science, pharmacy, and medicine, has seen influential publications mainly concentrated on targeted nanoparticles treatment for IBD. Keyword analysis revealed that current research hotspots include drug delivery, immune cell regulation, antioxidant damage, intestinal microbiota homeostasis, and nanovesicles.ConclusionThis study offers a comprehensive overview of global research landscape, emphasizing the rapid growth and increasing complexity of this field. It identifies key research hotspots and trends, including efforts to enhance the precision, efficacy, and safety of nanomedicine applications. Emerging directions are highlighted as crucial for further progress in this evolving area.